Mosaicode and the visual programming of web application for music and multimedia - Luiz Schiavoni, Flávio (2018)
The development of audio application demands a high knowledge about this application domain, traditional program- ming logic and programming languages. It is possible to use a Visual Programming Language to ease the application development, including experimentations and creative exploration of the language. In this paper we present a Visual Programming Environment to create Web Audio applications, called Mosaicode. Different from other audio creation platforms that use a visual approach, our environment is a source code generator based on code snippets to create complete applications.